Perbandingan Diksi Dalam Cerpen Klasik dan Modern - Rosdiana Rosdiana (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
The aim of this research is to explain the comparison of diction in classical and modern short stories. Short stories, as the name suggests, are short stories, requiring concise storytelling, without going into special details that are more likely to lengthen the story. This type of research is qualitative research because the data is in the form of a description of the comparison of classic and modern short story diction. In a short story, a piece of a character's life is told which is full of conflict, a touching or enjoyable event and contains an impression that is not easily forgotten. According to Muhardi and Hasanuddin WS (1992: 10-11) in novels and short stories both use the reverse highlighting technique. In short stories, flashbacks often deceive readers because they cannot be digested immediately, sometimes readers have to read more than once to make it easier to digest. Meanwhile, in novels the reverse highlighting technique is easier for readers to recognize. Classical and modern short stories are literary works that have differences. This difference can be seen and studied from the way it is distributed, namely that classical short story literary works develop from social culture, but are not bound by customs and modern short story literary works are usually written in books, bloggers and other intermediary media. The conclusion shows that the diction form of Modern Short Stories is more practical in choosing words, more in line with the general understanding of modern readers. Use words that are more current and widely known. And tend to choose classic words, with the use of words that are less common or ancient; Using appropriate diction and language style can develop children's imagination and knowledge of language.